Evaluation of a Plasmon-Based Optical Integrated Circuit for Error-Tolerant Streaming Applications - Samantha Lubaba Noor; Xuan Wu; Dennis Lin; Pol van Dorpe; Francky Catthoor; Patrick Reynaert; Azad Naeemi (IEEE Journal on Exploratory Solid-State Computational Devices and Circuits)
In this work, we have designed and modeled an integrated plasmonic computing module, which operates at 200 GHz clock frequency for high-end streaming algorithm applications. Our work includes designing the individual optical components (modulator, logic gate, and photodetector) and high-speed electronic driver circuits and integrating the components considering their interactions. We have also holistically evaluated the system-level performance of the computing module, taking into account various factors such as power consumption, operational speed, physical footprint, and average temperature. Through rigorous numerical analyses, we have found that with the existing technology and available materials, the plasmonic computing module can best achieve a bit-error-ratio (BER) of $10^{-1}$ . The performance can be improved by using a high electrooptic coefficient material in the phase shifter and increasing the driver circuit’s swing to greater than 1 V.